Commonalities and differences in trait-like, risky, and utilitarian decision-making styles between abstinent heroin-dependent individuals and their siblings - Yan, Wan-Sen; Lan, Yan; Liu, Su-Jiao (Frontiers in Psychiatry, 2026)
BackgroundHeroin dependence is associated with poor performance on laboratory-based decision-making paradigms. However, it remains unclear whether these deficits may have predated drug abuse due to potential familial susceptibilities or emerged as a consequence of chronic drug use. A family study may help clarify this important issue, so this study was to compare various decision-making aspects between heroin-dependent individuals and their siblings.MethodsA total of 70 abstinent heroin-dependent individuals (HAs), 69 unaffected biological siblings of the HAs (Siblings), and 74 unrelated healthy subjects (HCs) were included and tested on trait-like, risky, and utilitarian decision-making domains, using the Melbourne Decision-Making Questionnaire (MDMQ), the Balloon Analogue Risk Task (BART), and the Moral Decision-Making Task (MDMT).ResultsData indicated that both HAs and Siblings scored higher on MDMQ Procrastination (Cohen’s d = 0.61-1.17), and exhibited higher risk-taking levels (i.e., more pumps per trial and more explosions) on the BART (Cohen’s d = 0.39-1.25) compared with HCs. A lower level of competent decision-making (MDMQ Vigilance) and a higher ratio of utilitarian choices in self-involvement dilemmas were found in HAs, but not in Siblings, compared to HCs. Logistic regression models revealed homologous results.ConclusionsThese findings suggest that deficits in trait-like and risk-taking-related decision-making styles are shared by abstinent heroin-dependent individuals and their unaffected siblings, which might represent the conceivable markers for potential familial vulnerabilities implicated in the development of heroin dependence.